Labour market concentration, wages and job security in Europe - Bassanini, Andrea,Bovini, Giulia,Caroli, Eve,Casanova Ferrando, Jorge,Cingano, Federico,Falco, Paolo,Felgueroso, Florentino,Jansen, Marcel,Martins, Pedro S.,Melo, António,Oberfichtner, Michael,Popp, Martin (IZA - Institute of Labor Economics, 2022)
We investigate the impact of labour market concentration on two dimensions of job quality, namely wages and job security. We leverage rich administrative linked employer-employee data from Denmark, France, Germany, Italy, Portugal and Spain in the 2010s to provide the first comparable cross-country evidence in the literature. Controlling for productivity and local product market concentration, we show that the elasticities of wages with respect to labour market concentration are strikingly similar across countries: increasing labour market concentration by 10% reduces wages by 0.19% in Germany, 0.22% in France, 0.25% in Portugal and 0.29% in Denmark. Regarding job security, we find that an increase in labour market concentration by 10% reduces the probability of being hired on a permanent contract by 0.46% in France, 0.51% in Germany and 2.34% in Portugal. While not affecting this probability in Italy and Spain, labour market concentration significantly reduces the probability of being converted to a permanent contract once hired on a temporary one. Our results suggest that considering only the effect of labour market concentration on wages underestimates its overall impact on job quality and hence the resulting welfare loss for workers.
10419/263447
Keywords: Graue Literatur; labour market concentration; monopsony; wages; job security